2010
DOI: 10.1513/pats.201001-007aw
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying the Cellular Clearance of Antitrypsin Z: Lessons from Yeast Expression Systems

Abstract: The most frequent cause of a 1 -antitrypsin (here referred to as AT) deficiency is homozygosity for the AT-Z allele, which encodes AT-Z. Such individuals are at increased risk for liver disease due to the accumulation of aggregation-prone AT-Z in the endoplasmic reticulum of hepatocytes. However, the penetrance and severity of liver dysfunction in AT deficiency is variable, indicating that unknown genetic and environmental factors contribute to its occurrence. There is evidence that the rate of AT-Z degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Presumably, the residual Ssa proteins in ssa1,2 and ssa2,3,4 mutants support the degradation of particular substrates although they are not sufficient to fully restore the rate of overall proteolysis. Interestingly, a mutant form of yeast membrane ATPase also showed a similar pattern of dependence on different Ssa proteins for its degradation [17]. The degradation of the “N-end rule” substrate arginine-β-galactosidase (R-gal) was also reduced in ssa1-45 ts mutant (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Presumably, the residual Ssa proteins in ssa1,2 and ssa2,3,4 mutants support the degradation of particular substrates although they are not sufficient to fully restore the rate of overall proteolysis. Interestingly, a mutant form of yeast membrane ATPase also showed a similar pattern of dependence on different Ssa proteins for its degradation [17]. The degradation of the “N-end rule” substrate arginine-β-galactosidase (R-gal) was also reduced in ssa1-45 ts mutant (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Since then, AAT-Z and another mutant form of AAT, known as null Hong Kong (NHK), have been heavily utilized as model ERAD substrates, and much of what is now understood about the quality control of glycosylated proteins in the ER has been derived from the use of the NHK variant. It should also be noted that AAT-Z is a substrate that can be disposed of by multiple degradation pathways [132]. While AAT-Z was one of the model substrates to first demonstrate the existence of ERAD, it has also clearly been shown that AAT-Z enters the autophagy pathway and is degraded in the lysosome [133, 134].…”
Section: The Early History Of the Erad Pathwaymentioning
confidence: 99%
“…Reports have suggested that accumulation of ZAAT polymers within the ER of hepatocytes activates proteasomal and autophagic degradation pathways [Perlmutter, 2006;Kroeger et al, 2009;Gelling and Brodsky, 2010;Ghouse et al, 2014]. Chaperones interacting with ZAAT in the ER include calnexin, protein-disulfide isomerase, GRP-78/BiP, EDEM1, and the N-glycan-modifying enzymes UDP-glucose: glycoprotein glucosyltransferase and a-mannosidase-like protein [Cabral et al, 2002;Schmidt and Perlmutter, 2005;Granell et al, 2008;Jang et al, 2015].…”
mentioning
confidence: 99%